The Use of Fraction Tiles as Manipulative Media in Fraction Learning to Improve Algebraic Thinking Skills of Fourth Grade Elementary School Students - Putri Indah Sari, Cut; Salma Amira Miftahul Jannah; Talitha Lillian Harvani Santoso; Manggali Revalitanaya; Elsa Nurmala Sari; Evi Faujiah (Universitas Pekalongan, 2025)
Algebraic thinking is a fundamental mathematical ability that supports students’ understanding of relationships, patterns, and structures, particularly in learning fractions at the elementary school level. This study aimed to examine the effectiveness of using Fraction Tiles as manipulative media in fraction learning to enhance fourth-grade students’ algebraic thinking skills. A pre-experimental method with a one-group pretest–posttest design was employed involving 30 elementary school students. The learning activities emphasized concrete manipulation, visual representation, pattern exploration, and symbolic expression of fraction relationships using Fraction Tiles. Students’ algebraic thinking abilities were assessed across four indicators: identifying equivalence and relationships among fractions, representing fractions in multiple forms, drawing simple generalizations from fraction patterns, and using mathematical symbols to express relationships. Data were analyzed using descriptive statistics and a paired-samples t-test. The results revealed a substantial improvement in students’ algebraic thinking, as indicated by higher mean posttest scores compared to pretest scores. The paired-samples t-test showed a statistically significant difference (p < 0.001), accompanied by a very large effect size (Cohen’s d = −48.0), indicating strong practical effectiveness. These findings suggest that the use of Fraction Tiles is highly effective in fostering algebraic thinking and provides a meaningful instructional approach for fraction learning in elementary education.